Analysis of Factors Influencing the Productivity of Inpatient Nurses at Mitra Medika Premiere Hospital - Annisa Fadhillah Nasution; Chrismis Novalinda Ginting; Ali Napiah Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The productivity of nurses, being the frontline of healthcare services, is a crucial issue for maintaining and enhancing the quality of healthcare services. High productivity of nurses serves as a bridge to ensure the quality of healthcare services provided to both sick and healthy patients. This study aims to analyze the factors that influence the productivity of inpatient nurses at Mitra Medika Premiere Hospital. This research is an observational analytic study with a cross-sectional design. The study was conducted at Mitra Medika Premiere Hospital from November 2023 to March 2024. The population consists of all inpatient nurses at Mitra Medika Premiere Hospital, totaling 70 nurses, and the sample size is also 70 nurses. The sampling technique employed was total sampling. Data collection was done using primary data obtained from respondents through questionnaires. The data analysis consisted of three stages: univariate analysis using frequency, bivariate analysis using chi-square tests, and multivariate analysis using multiple logistic regression tests with a 95% significance level (α = 0.05). The results of the study indicate that the factors influencing the productivity of inpatient nurses at Mitra Medika Premiere Hospital are gender (p-value=0.036; ExpB=3.094), working hours (p-value=0.001; ExpB=17.832), and workload (p-value=0.012; ExpB=5.743). Gender, working hours, and workload significantly contribute to the productivity of inpatient nurses at Mitra Medika Premiere Hospital. The most dominant factor influencing the productivity of inpatient nurses is working hours. Recommendations for Hospital include reducing working hours, as shorter working hours can enhance concentration and motivation, thereby increasing nurse productivity. Additionally, reducing tasks and responsibilities can alleviate the workload of nursesKeywords: Inpatient, Nurses, Productivity